2020
DOI: 10.1002/adfm.201910464
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Mechanism of Perovskite Light‐Emitting Diodes: An In Situ Investigation via Electroabsorption Spectroscopy and Device Modelling

Abstract: The past few years have seen a significant improvement in the efficiency of organometal halide-perovskite-based light-emitting diodes (PeLEDs). However, poor operation stability of the devices still hinders the commercialization of this technology for practical applications. Despite extensive studies on the degradation mechanisms of perovskite thin films, it remains unclear where and how degradation occurs in a PeLED. Electroabsorption (EA) spectroscopy is applied to study the degradation process of PeLEDs dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 53 publications
0
46
0
1
Order By: Relevance
“…It can be observed in many PeLEDs in literature during lifetime measurements, with the stressing time spanning a wide range of timescales from few minutes to several hours. [ 8,20,21 ]…”
Section: Figurementioning
confidence: 99%
“…It can be observed in many PeLEDs in literature during lifetime measurements, with the stressing time spanning a wide range of timescales from few minutes to several hours. [ 8,20,21 ]…”
Section: Figurementioning
confidence: 99%
“… 27 ). In our previous study 28 , we found that the ion diffusion at the interface between the perovskite and its top neighboring organic hole-transporting layer plays a critical role in the degradation process of PeLEDs. It is worth noting that to date almost all surface passivation or ligand engineering research of PeLEDs focuses on defect passivation, instead of ion-blocking.…”
Section: Introductionmentioning
confidence: 96%
“…15,16 In addition, based on previous investigations of perovskite solar cells, field-dependent ion migration and relevant material/interfacial degradation have been regarded as the most critical factors limiting the reliability of PeLEDs. [17][18][19][20][21] As such, there have been extensive efforts to improve the operational lifetime by immobilizing the ions, including perovskite composition engineering, 22 defect passivation, and construction of mixed-dimensional structures. 3,5,[23][24][25] Nevertheless, a deep understanding of how ion-drifting influences PeLEDs' performance in detail remains missing, hindering targeted material design and device optimization for further improvement of the operational lifetime.…”
Section: Introductionmentioning
confidence: 99%